S05-1 Cultural adaptation and validation of the copsoq ISTAS21 questionnaire in argentina. (1st September 2016) - Gerke, Johanna; Cornelio, Cecilia; Zelaschi, Constanza; Alberto, Marcos; Amable, Marcelo; Contreras, Adela; Reif, Luciana
Abstract : The relevance of the psychosocial factors and occupational health is increasing worldwide. In Argentina a robust measuring instrument of them is needed. The COPSOQ (Copenhagen Psychosocial Questionnaire) is a comprehensive instrument for its assessment, and it was currently adapted in several countries. The Union Institute of Work Environment and Health (ISTAS) got its Spanish version, known as COPSOQ ISTAS 21. We founded our study on the updated long version of this questionnaire (95 items). The aims of the study were the semantic adaptation through a qualitative strategy, the detailed validation of the psychometric measurement properties, and the development of an abbreviated version of the instrument. We used an intentional sample with a maximum variation strategy, until we reached the theoretical saturation. The main criterion used to set the sample was the educational level (combined with sex and age). With a random sample of 200 wage-earners we performed the quantitative analysis of content validity, reliability, criterion validity and sensitivity. The cultural adaptation, reached by the analyses of the interpretational expected and emerged difficulties, provided us an acceptable and clear version of the questionnaire in our context. For the principal dimensions the Cronbach's alpha was mostly >0.7 (Demands 0.86, Double presence 0.75, Work organisation 0.83, Interpersonal relationships and leaderships 0.88, Insecurity 0.84, Confidence 0.68, Justice 0.84). The factorial analysis was also consistent. In addition, these psychometric properties were comparable to those in the Danish and German COPSOQ-studies. The adapted Argentinian version is comparable with the COPSOQ ISTAS 21 instrument in terms of validity and is suitable for assessment of the psychosocial work environment in Argentina. The next step is the construction of national reference values for its preventive use in our country.